2017
DOI: 10.18632/oncotarget.15284
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral lactate metabolism in Barrett's esophagus and adenocarcinoma

Abstract: BackgroundMonocarboxylate transporters (MCTs) are cell membrane proteins which transport pyruvate, lactate and ketone bodies across the plasma membrane. MCTs are activated in various cancers, but their expression in esophageal adenocarcinoma is not known. The present study was conducted to elucidate the expression of MCTs in esophageal adenocarcinoma and its precursor lesions.ResultsCytoplasmic MCT1, MCT4 and MTCO1 expression linearly increased from normal epithelium to Barrett's mucosa to dysplasia and cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…In Xenopus oocytes, CAII has a noncatalytic function as a facilitator of transmembrane ion shuttles [13], such as the monocarboxylate transporters MCT1 and MCT4. These transporters of high energy metabolites, such as lactate, are upregulated in EAC [42] and various other carcinomas. Altogether, these data suggest the mechanisms linking downregulation of CAII and metastatic behaviour should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…In Xenopus oocytes, CAII has a noncatalytic function as a facilitator of transmembrane ion shuttles [13], such as the monocarboxylate transporters MCT1 and MCT4. These transporters of high energy metabolites, such as lactate, are upregulated in EAC [42] and various other carcinomas. Altogether, these data suggest the mechanisms linking downregulation of CAII and metastatic behaviour should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…The role of mitochondrial ribosomal protein S23 (MRPS23) in carcinoma cell proliferation could be a potential therapeutic target, in case of interference of hepatocellular cancer proliferation, oncogenesis and metastasis (Pu et al 2017). The expression of COX1 was involved in endometrial cancers (Ksiezakowska-Lakoma et al 2017), esophageal adenocarcinoma (Huhta et al 2017) and lung cancer (Michalak et al 2016). Taken all together, these examples support the notion that mitochondria contribute to the angiogenetic, tumorigenic, proliferation, invasive and metastatic features of cancer cells.…”
Section: Introductionmentioning
confidence: 66%
“…In stark contrast, physiologically, MCT4 was found to be in charge of efflux of lactate, as systemically reviewed by Halestrap AP [16]. Although extensive studies can be readily available regarding the MCT1 in cancers of different types; it has been little described in esophageal cancer with the exception of two recent related reports [17,18]: one about MCT1 expression in Barrett's esophagus and adenocarcinoma, the other ESCC. Analysis from previous investigations concerning MCT1 in cancers, regardless of different types [19][20][21][22], revealed that MCT1 prevailed or predominantly over-expressed in cancerous tissues as compared with normal controls and up-regulated MCT1 was found to be linked with poor outcome as well as tumor metastases, which was fully in agreement with our observations in ESCC of our own case.…”
Section: Discussionmentioning
confidence: 99%
“…Studies undertaken in the area of cancer abound, unraveling that MCT4 was uniformly seen to be strikingly up-regulated in cancerous tissues compared with normal control; and elevated MCT4 was correlated with unfavorable outcome [19,21,[24][25][26]. By contrast, there were only two pieces of literature with regard to MCT4 in esophageal cancer until now [17,27]. In our findings, MCT4 was exhibited to be an independent prognostic factor of ESCC, whereas no significant correlation with lymph nodes metastases was observed, was partly supported by the replicated observation made by Cheng B et al in ESCC [27].…”
Section: Discussionmentioning
confidence: 99%